Processing of Keratin Waste of Meat Industry - Mokrejs, P.; Hrncirik2, J.; Janacova3, D.; Svoboda1, P. (Asian Journal of Chemistry, 2011)
Chicken feathers were processed through hydrolysis in two stages and breakdown efficiency was monitored by factor tests. In the first stage, feathers were incubated in an environment of 0.1 % or 0.3 % aqueous solution of KOH (ratio 1:50) for 24 h at 70 ºC. After adapting pH level to 9, action by proteolytic enzyme polarzyme 12 T (1-5 %, w/w) at temperature 30-50 ºC broke down the feathers in 4-8 h into keratin hydrolyzate. Hydrolysis of feathers in environment of 0.1 % KOH is quite low (max. 20 %). In an environment of 0.3 % KOH the hydrolysis efficiency is more than four-fold. At upper limits of factors under study (8 h hydrolysis at 50 ºC with 5 % addition of enzyme) 88.7 % feathers were degraded. Test results confirmed that applying proteolytic enzyme polarzyme 12 T achieved efficiency of chicken feather degradation similar to formerly used enzyme Savinase Ultra 16 L.